Classroom assessment approaches and student learning outcomes: the moderating role of teaching experience - Polemer M. Cuarto; Harieth C. Cuarto (Journal of Education and Learning (EduLearn), 2026)
Maximizing student learning requires the use of effective classroom assessment. In this study, we examined the association between student learning outcomes (SLOs) and three classroom assessment approaches: assessment as learning (AaL), assessment for learning (AfL), and assessment of learning (AoL), while taking teacher experience into account as a potential moderator. Positive correlations between all three assessment techniques and SLOs were found in the research, suggesting that classrooms emphasizing student participation in assessment to receive feedback and improve learning achieve better outcomes. Interestingly, we uncover that teaching experience did not moderate this relationship, indicating that the positive effects of these practices were consistent across teachers with varying levels of experience within the studied range. Our findings emphasize the importance of incorporating comprehensive assessment practices encompassing AaL, AoL, and AfL into classroom instruction to optimize student learning. Future research should explore reasons behind differences in effect size and explore deeper into specific strategies most beneficial for each approach to create learning environment that foster deep learning for all students, regardless of teacher experience.